2023
DOI: 10.3390/ijerph20031782
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Expectations of Academic Staff in Bucharest towards the COVID-19 Pandemic Impact on Dental Education

Abstract: Dental education was severely challenged by the COVID-19 pandemic worldwide. The evaluation of the viewpoint of the dental teachers of the Faculty of Dentistry at “Carol Davila” University of Medicine and Pharmacy in Bucharest, Romania, on these exceptional circumstances’ consequences was the objective of this paper. A cross-sectional study was conducted in April 2022, on the academic staff who reported their perceptions of the emotional and educational impact of the pandemic by completing a Google Forms quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Healthcare workers from various domains, neonatology, oncology, and especially the ones from the dentistry, are at great risk for flu and COVID-19 exposure, as they may be a source of flurona spread, as studies had revealed [61][62][63][64]. Vaccination may have side effects [65,66] that cause further burden for people, especially healthcare workers.…”
Section: Plos Onementioning
confidence: 99%
“…Healthcare workers from various domains, neonatology, oncology, and especially the ones from the dentistry, are at great risk for flu and COVID-19 exposure, as they may be a source of flurona spread, as studies had revealed [61][62][63][64]. Vaccination may have side effects [65,66] that cause further burden for people, especially healthcare workers.…”
Section: Plos Onementioning
confidence: 99%
“…The COVID-19 pandemic had a negative impact on sustainability in dentistry, health professionals considerably increasing their usage of PPE materials, as a result of the pandemic, in order to lower the risk of infections [62]. On the other hand, it was demonstrated that dental staff, academic personnel, dental students and dental researchers were affected by the COVID-19 pandemic on multiple levels (such as economic, financial, social and emotional status) [63][64][65][66][67][68].…”
Section: Dentists' Opinion Regarding the Most Effective Approaches Fo...mentioning
confidence: 99%